Executive Control of Emotional Conflict - Boncompagni, Ilaria; Casagrande, Maria (Frontiers in Psychology, 2019)
Attentional networks and their interactions have been extensively studied through the Attentional Network Test for Interaction (ANTI). This task combines a spatial cueing paradigm with a flanker procedure and examines the efficiency and the interactions among the attentional networks (Alerting, Orienting and Executive control). However, the ANTI did not consider the effect of emotions on the attentional systems, although many studies have shown a relationship between emotion and Executive system. This study aims to analyze the executive system in an emotional context. We used a version of ANTI with arrows (ANTI-A) and an ANTI-Emotion (ANTI-E), where the arrows in the flanker task were replaced with neutral and threatening faces. One hundred and thirty-four university students performed both an ANTI-A and an ANTI-E. Results confirmed all the main effects and interactions for both the types of ANTI. Furthermore, the ANTI-E showed that the executive control of the conflict was harder when the target was neutral rather than when it was threatening. This difficulty in solving the flanker task could be due to the effect of distractors with a threatening valence. The ANTI-E could be allowed to verify how much attentional bias that characterizes people with emotional disorders (e.g., anxiety) may depend on altered executive control of the emotional conflict.